2012
DOI: 10.1007/s10484-012-9204-3
|View full text |Cite
|
Sign up to set email alerts
|

Is EEG-biofeedback an Effective Treatment in Autism Spectrum Disorders? A Randomized Controlled Trial

Abstract: EEG-biofeedback has been reported to reduce symptoms of autism spectrum disorders (ASD) in several studies. However, these studies did not control for nonspecific effects of EEG-biofeedback and did not distinguish between participants who succeeded in influencing their own EEG activity and participants who did not. To overcome these methodological shortcomings, this study evaluated the effects of EEG-biofeedback in ASD in a randomized pretest-posttest control group design with blinded active comparator and six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 41 publications
2
34
0
5
Order By: Relevance
“…Specifically, it has been found that EEG learning is closely related to the improvement of performance after training in a variety of NF protocols (Egner and Gruzelier, 2003; Ros et al, 2009; Keizer et al, 2010; Nan et al, 2012; Gruzelier, 2014a), and it influences the transfer effects of NF from laboratory to real-world conditions (Sitaram et al, 2017). Although many trainees can gain successful learning to regulate the brain activity of interest in a desired direction, a substantial portion of subjects have been reported unsuccessful in EEG learning, regardless of the NF protocol and subject population (Lubar et al, 1995; Kotchoubey et al, 1999; Hanslmayr et al, 2005; Kropotov et al, 2005; Doehnert et al, 2008; Weber et al, 2011; Zoefel et al, 2011; Kouijzer et al, 2013; Enriquez-Geppert et al, 2014; Schabus et al, 2014; Reichert et al, 2015; Baumeister et al, 2016; Hsueh et al, 2016; Quaedflieg et al, 2016). The rates of this type of so-called non-learners vary, up to around 50% in some studies (Hanslmayr et al, 2005; Doehnert et al, 2008; Okumura et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it has been found that EEG learning is closely related to the improvement of performance after training in a variety of NF protocols (Egner and Gruzelier, 2003; Ros et al, 2009; Keizer et al, 2010; Nan et al, 2012; Gruzelier, 2014a), and it influences the transfer effects of NF from laboratory to real-world conditions (Sitaram et al, 2017). Although many trainees can gain successful learning to regulate the brain activity of interest in a desired direction, a substantial portion of subjects have been reported unsuccessful in EEG learning, regardless of the NF protocol and subject population (Lubar et al, 1995; Kotchoubey et al, 1999; Hanslmayr et al, 2005; Kropotov et al, 2005; Doehnert et al, 2008; Weber et al, 2011; Zoefel et al, 2011; Kouijzer et al, 2013; Enriquez-Geppert et al, 2014; Schabus et al, 2014; Reichert et al, 2015; Baumeister et al, 2016; Hsueh et al, 2016; Quaedflieg et al, 2016). The rates of this type of so-called non-learners vary, up to around 50% in some studies (Hanslmayr et al, 2005; Doehnert et al, 2008; Okumura et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The rates of this type of so-called non-learners vary, up to around 50% in some studies (Hanslmayr et al, 2005; Doehnert et al, 2008; Okumura et al, 2017). What is more, the non-learners often show less improvement on behavior/symptoms than learners (Lubar et al, 1995; Kropotov et al, 2005) or even no improvement after NF training (Hanslmayr et al, 2005; Kouijzer et al, 2013; Hsueh et al, 2016), which seriously affects the efficacy of NF training.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kouijzer et al (2013) showed no difference in effect between EEG biofeedback and skin conductance biofeedback, but both were better in reducing autistic symptoms as compared to a nontreatment control group. They concluded that the beneficial effects might be due to treatment expectancy, implicit training of attention and/or intensive one-to-one contact with a therapist.…”
Section: Discussionmentioning
confidence: 89%
“…Others have recently hypothesized that the positive effects of neurofeedback for individuals with autism might be due to non-specific factors (Heinrich, Gevensleben, & Strehl, 2007;Kouijzer, van Schie, Gerrits, Buitelaar, & de Moor, 2013). For example, Kouijzer et al (2013) showed no difference in effect between EEG biofeedback and skin conductance biofeedback, but both were better in reducing autistic symptoms as compared to a nontreatment control group.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the papers published are case or multiple case reports, with only a few randomized controlled studies. [10][11][12][13][14][15][16][17][18][19] Shorter-term studies are commonly used in medical research as a form of clinical trial, or a means to test a particular hypothesis of clinical importance. Such studies typically follow two groups of patients for a period of time and compare an endpoint or outcome measure between the two.…”
mentioning
confidence: 99%